Applying IMC and PENCILS Framework: Marketing Communication Strategy for Customer Retention in Local Coffee Shop - Dian Salssabil Al Malik; Firdaus Yuni Dharta; Oky Oxcygentri (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
This study aims to analyze the conventional marketing communication strategy implemented by Kedai 20 Kopi Karawang in maintaining customer loyalty. Using a qualitative descriptive approach, data were collected through in-depth interviews with five informants (owner, manager, marketing staff, barista, cashier), observation, and documentation. The findings indicate that Kedai 20 Kopi applies Integrated Marketing Communication (IMC) principles by integrating personal message strategies and conventional media with digital channels. The PENCILS concept (Publications, Events, News, Community Involvement, Identity Tools, Lobbying, Social Investment) is utilized to enhance brand image and emotional closeness with customers. The Four Step model (Fact Finding, Planning, Communication, Evaluation) is implemented systematically in planning and evaluating marketing strategies. Supporting factors include a solid team, strategic location, and community support, while constraints include limited resources, high competition, and challenges in maintaining message consistency. This research contributes to the development of marketing communication science, particularly regarding the integration of conventional and digital strategies in the coffee shop industry